Advanced donor age does not increase risk of hepatocellular carcinoma recurrence after liver transplantation: a retrospective two‐centre analysis using competing risk analysis. (27th July 2021) - Cusumano, Caterina; De Carlis, Luciano; Centonze, Leonardo; Lesourd, Romain; Levi Sandri, Giovanni Battista; Lauterio, Andrea; De Carlis, Riccardo; Ferla, Fabio; Di Sandro, Stefano; Camus, Christophe; Jézéquel, Caroline; Bardou‐Jacquet, Edouard; et al.
Summary: The impact of donor age on the recurrence of hepatocellular carcinoma (HCC) after liver transplantation is still debated. Between 2002 and 2014, all patients transplanted for HCC in 2 European liver transplantation tertiary centres were retrospectively reviewed. Risk factors for HCC recurrence were assessed using competing risk analysis, and the impact of donor age < or ≥65 years and < or ≥80 years was specifically evaluated after propensity score matching. 728 patients transplanted with a median follow‐up of 86 months were analysed. The 1‐, 3‐ and 5‐year recurrence rates were 4.9%, 10.7% and 13.9%, respectively. In multivariable analysis, recipient age (sHR: 0.96 [0.93; 0.98], P  < 0.01), number of lesions (sHR: 1.05 [1.04; 1.06], P  < 0.001), maximum size of the lesions (sHR: 1.37 [1.27; 1.48], P  < 0.01), presence of a hepatocholangiocarcinoma (sHR: 6.47 [2.91; 14.38], P  < 0.01) and microvascular invasion (sHR: 3.48 [2.42; 5.02], P  < 0.01) were significantly associated with HCC recurrence. After propensity score matching, neither donor age ≥65 ( P  = 0.29) nor donor age ≥80 ( P  = 0.84) years increased the risk of HCC recurrence. In conclusion, donor age was not found to be a risk factor for HCC recurrence. Patients listed for HCC can receive a graft from an elderly donor without compromising the outcome.